PENURUNAN DISMENOREA DENGAN PEMBERIAN STIMULUS KUTANEUS - Sulistiyowati Sulistiyowati (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2019)
Abstract Dysmenorrhea is a pain occurred before or during menstruation which is usually in the lower abdomen forcing the sufferers to rest. The research problem was the high incidence of dysmenorrhea that disrupts activity. The aim of the study was to determine the effect of cutaneous stimulation on decreasing dysmenorrhea in young women. Pre-experimental study with an approach (One Group Pre-Post Test Design) was used with population of all young women who live in the complex of SMK Al-Futuh Tikung, Lamongan who experienced dysmenorrhea in 2017/2018 and the sample were 30 young women. The independent variable was giving cutaneous stimulation and the dependent variable was the decreasing in dysminorrhoea. Concecutive sampling technique was used using VAS scale measurement tool. It was analyzed using Paired Sample T-Test with a significant level of p <0.05. The results showed that the majority of young women experienced dysmenorrhea before the application of cutaneous stimulation and the a lot of them did not experience dysmenorrhea after cutaneous stimulation was given. There were differences in the level of dysmenorrhea before and after applying cutaneous stimulation, with t = 45,639 and p = 0,000. Looking at the results of this study, cutaneous stimulation can be effectively used to reduce dysmenorrhea. Kata Kunci : Dysmenorrhea, stimulation, cutaneous